2014
DOI: 10.14260/jemds/2014/2982
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Gall Bladder Carcinoma in Patients Undergoing Laparoscopic Cholecystectomy

Abstract: BACKGROUND: Gall stones are the most common biliary pathology. Cholelithiasis, whether symptomatic or asymptomatic, needs cholecystectomy due to 70-98% association of gall bladder carcinoma with gall stones. Despite this, the prevalence of carcinoma gall bladder is 2-5% with 0.3-0.5% being incidentally diagnosed in patients undergoing cholecystectomy. In such cases, clinical judgment and high index of suspicion in a rural setup is a worthy tool. AIMS AND OBJECTIVES: The study was undertaken to determine incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Very few lesions were found to have no associated cholelithiasis. (6) Similarly, Gupta et al (7) also found high prevalence of gall stones in all GB lesions. In concordance with the literature, we found gallstones in 3 of the 5(75%) cases of GB adenomas, 100% cases of isolated dysplasia and 9 of the 10(90%) cases of GBC.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Very few lesions were found to have no associated cholelithiasis. (6) Similarly, Gupta et al (7) also found high prevalence of gall stones in all GB lesions. In concordance with the literature, we found gallstones in 3 of the 5(75%) cases of GB adenomas, 100% cases of isolated dysplasia and 9 of the 10(90%) cases of GBC.…”
Section: Discussionmentioning
confidence: 87%
“…In our study 90% cases of GBC had associated gall stones, as observed by other authors. (3)(4)(5)(6)(7) Bhawna et al in their study have also illustrated that GB dysplasia, tubular adenomas, carcinoma in situ and invasive carcinoma were frequently associated with gall stones. Very few lesions were found to have no associated cholelithiasis.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation